Pelindungan Hukum Terhadap Penerapan Prosedur Keselamatan dan Kesehatan Kerja pada Pekerja PT. Sagatrade Murni Kota Samarinda - Arifin, Alziqry; Pratama, Rio Arif (Universitas Muhammadiyah Yogyakarta, 2025)
The era of globalization and increasingly competitive developments require companies to maximize resources to create high-quality products. One of them is by having strong human resources (HR). Legal protection for the implementation of Occupational Safety and Health (K3) procedures is a crucial aspect in maintaining worker welfare and the sustainability of company operations as well as the supervisory function carried out by the government. This research was conducted empirically with primary and secondary data. The data was collected through literature studies and interviews with related parties through descriptive analysis and qualitative approaches. This study aims to determine the protection provided by the company for the implementation of K3 and the role of labor inspectors in the process. The results of this study indicate that the company has provided good protection to its workers including the provision of Personal Protective Equipment (PPE) in accordance with the Standard Operating Procedure (SOP). The role of the government in carrying out supervision and coaching is attempted to run optimally so that it can continue to be improved. This study emphasizes the importance of synergy between internal company protection and external supervision from the government to ensure the achievement of maximum occupational safety and health goals.